1999
DOI: 10.1083/jcb.146.2.389
|View full text |Cite
|
Sign up to set email alerts
|

Shc and Fak Differentially Regulate Cell Motility and Directionality Modulated by Pten

Abstract: Cell migration is modulated by regulatory molecules such as growth factors, oncogenes, and the tumor suppressor PTEN. We previously described inhibition of cell migration by PTEN and restoration of motility by focal adhesion kinase (FAK) and p130 Crk-associated substrate (p130Cas). We now report a novel pathway regulating random cell motility involving Shc and mitogen-activated protein (MAP) kinase, which is downmodulated by PTEN and additive to a FAK pathway regulating directional migration. Overexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
279
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(291 citation statements)
references
References 72 publications
10
279
0
2
Order By: Relevance
“…One substrate for Erks that can lead to motility and changes in actin organization is myosin light chain kinase (Klemke et al, 1997). Additionally, recent work showed that both FAK and Shc could work through Erks to promote integrin-mediated cell migration and cytoskeletal organization (Gu et al, 1999). A role for MAP kinase and c-Abl in integrin signaling is therefore consistent with the altered cell migration and cytoskeletal organization observed in cAbl-de®cient mice (Koleske et al, 1998).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…One substrate for Erks that can lead to motility and changes in actin organization is myosin light chain kinase (Klemke et al, 1997). Additionally, recent work showed that both FAK and Shc could work through Erks to promote integrin-mediated cell migration and cytoskeletal organization (Gu et al, 1999). A role for MAP kinase and c-Abl in integrin signaling is therefore consistent with the altered cell migration and cytoskeletal organization observed in cAbl-de®cient mice (Koleske et al, 1998).…”
mentioning
confidence: 67%
“…However, the activation of Erks when cells are replated on FN is highly transient and is therefore unlikely to promote progression through G1. Integrin activation of MAP kinase has also been implicated in cytoskeletal organization and cell migration (Anand-Apte et al, 1997; Klemke et al, 1997;Gu et al, 1999). One substrate for Erks that can lead to motility and changes in actin organization is myosin light chain kinase (Klemke et al, 1997).…”
mentioning
confidence: 99%
“…Activation of NF-κB leads to suppression or activation of PTEN expression depending on the stimulus and the cell type [31,32]. We previously demonstrated that IL-18 stimulates PTEN induction in EC via NF-κB-activation [12].…”
Section: Il-18 Stimulates Pten Transcriptionmentioning
confidence: 99%
“…Focal adhesion kinase (FAK) is a nonreceptor tyrosine kinase critical for the formation of focal adhesion complexes (FAC) and cell spreading, motility and survival [12]. FAK is a substrate of Src, and both FAK and Src are activated in cancer cells overexpressing erbB2 or stimulated with erbB ligand [13,14].…”
Section: Introductionmentioning
confidence: 99%